Effectivity Of Multi Tray Aerator As Pretreatment Process For Reverse Osmosis Membrane To Utilized As Raw Water At Sungai Itik Village - Septiansyah, Edo; Purnaini, Rizki; Danial, Mochammad Meddy (Jurnal Teknologi, 2024)
The community in Sungai Itik Village and its vicinity use river water for their daily needs, such as irrigation for agriculture, fish ponds, washing, bathing, and more. The quality of the river water has an iron (Fe) content of 2,64 mg/L, Total Dissolved Oxygen (TDS) of 347 mg/L, Dissolved Oxygen (DO) of 4,7 mg/L, a temperature of 29°C, and a pH of 5,4. The iron (Fe) content exceeds the standards set by PerMenKes No. 32 of 2017, requiring treatment using a multiple-tray aerator. This study aimed to determine the effective distance and number of trays in treating Sungai Itik's raw water, understand the coefficient of gas transfer (KLa) in the aeration process, and find the optimum aeration time. This study employed a multiple-tray aerator consisting of 5 trays with variations in the tray distances at 30 cm, 40 cm, 50 cm, and 60 cm. Three repetitions were performed for each treatment, both without gravel and with gravel. The results of this study showed that the best reduction in Fe content was achieved by the treatment with gravel at a tray distance of 60 cm using 5 trays, resulting in a 6,64% reduction in Fe from an average value of 1,51 mg/L to 1,41 mg/L. The average pH value was 6,19, and the TDS was 890 mg/L. The highest oxygen transfer rate (KLa) was obtained at a tray distance of 60 cm with gravel, averaging 0,2857/minute, and the optimum aeration time was 10 minutes.